Virucides in apiculture: persistence of surrogate enterovirus under simulated field conditions. Issue 12 (22nd August 2017) - Prodělalová, Jana; Malenovská, Hana; Moutelíková, Romana; Titěra, Dalibor
Abstract: BACKGROUND: Honeybee viruses have been recognized as being among the most important factors leading to colony losses worldwide. Colony food and faeces are regarded as possible sources of infectious viruses able to contaminate the environment and equipment of apiaries. Thus, methods for elimination of viruses are required. No cell culture assay for testing the effect of disinfectants on honeybee viruses is yet available. Therefore, surrogate virus was employed for testing of the efficacy of iodophor‐ and peracetic acid‐based disinfectants in combination with six organic contaminants at +6 °C and +22 °C. Moreover, we evaluated the persistence of the surrogate in honey at +6 °C, +22 °C, and +50 °C. RESULTS: Iodophor‐based disinfectant showed a maximum reduction of virus titre of 3.4 log10 . Peracetic acid reduced the titre (≥4 log10 ) only at 22 °C and without yeast extract/bovine serum albumin. After 25 days of incubation of the virus − honey mix, no decrease of virus titre was observed at +6 °C, whereas a significant reduction (3.5 log10 ) was found at +50 °C already after 1 day. CONCLUSIONS: Both tested disinfectants can serve as appropriate virucides in apiaries. The effect of peracetic acid significantly depended on temperature and organic contaminants. The iodophor‐based disinfectant showed a stable antiviral effect at different temperatures and with different contaminants. © 2017 Society of Chemical Industry